IMPACT OF COVID-19 ON E-LEARNING THROUGH SWAYAM MOOCS: AN EDUCATIONAL STUDY IN INDIA” - Amitharani (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The impact of COVID-19 pandemic is observed in every nook and corner of the world, in each and every sector right from the health, business, economy, information technology and education etc. The COVID-19 pandemic has been badly disrupted the education system in India. To eradicate this serious issue of educational disruption due to the COVID-19 pandemic, the only way to establish a consistent structure for the next course of action is to transition to e-learning, where both teachers and students need to turn to a digital platform. India has started various projects for offering MOOC courses. SWAYAM plays a major role among them. SWAYAM is a programme initiated by the Government of India. This paper discusses the different features of the SWAYAM platform. The study also differentiates the concept of SWAYAM. SWAYAM is an ethnic IT Platform for hosting the MOOCs (Massive Open Online Courses). The geographical, sociological and political barriers in education can be overlooked by making MOOCs as similar to regular school education.